Assessment and analysis of polymyxin sensitivity using the disc elution method on clinical isolates resistant to carbapenems - Awan, Muhammad Raheel; Sabir, Maimoona; Shoukani, Hussan ibne; Nasir, Nimra; Khalil, Sadia; Asif, Misbah; Zaman, Faisal (International Journal of Applied and Experimental Biology, 2026)
Elevated mortality rates have drawn the focus of researchers to multidrug-resistant Gram-negative Enterobacteriaceae over the last decade. In the case of multidrug-resistant Gram-negative bacteria, particularly carbapenem-resistant Enterobacteriaceae (Enterobacterales), polymyxin B stands as one of the last-resort antibiotics. This study aimed to evaluate clinical isolates of Gram-negative bacteria displaying resistance to carbapenems and subjected them to polymyxin B using the disc diffusion method. Clinical specimens were gathered from various anatomical sites, and bacterial isolates were obtained through culturing. After isolation, biochemical testing was conducted for bacterial identification. The identified isolates were then subjected to antibiotic susceptibility testing, employing the Kirby-Bauer Disc Diffusion technique. A comparative analysis was undertaken between the disc elution method and the disc diffusion method, with validation against the reference Broth Microdilution (BMD) technique. A total of one hundred and fifty-two (152) clinical specimens were obtained. The isolates primarily comprised Klebsiella pneumoniae (n = 49), Escherichia coli (n = 41), Pseudomonas aeruginosa (n = 31), Acinetobacter baumannii (n = 29), and Proteus vulgaris (n = 02). Diverse specimen types were collected from various patient sites, encompassing pus swabs (n = 82), urine (n = 36), tracheal tubes (n = 12), sputum (n = 11), blood cultures (n = 6), bronchial washings (n = 2), high vaginal swabs (n = 2), and cerebrospinal fluid (n = 1). The distribution of patients was categorized by gender, with 95 females and 57 males. The majority of the strains were identified in patients aged between 41 and 60 years. The disc elution method categorized 127 samples as susceptible, 13 as intermediate, and 12 as resistant to polymyxin B, while the disc diffusion method labeled 128 samples as susceptible and 24 as resistant. In routine antimicrobial susceptibility testing, the disc diffusion method is commonly used for polymyxin B, even though it is not recommended by CLSI. This study concludes that the disc elution method, recommended by CLSI, demonstrates superior accuracy, precision, and sensitivity in detecting susceptibility to polymyxin B compared to the disc diffusion method.